1997
DOI: 10.1056/nejm199709253371303
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Drainage Compared with Surgery for Hepatic Hydatid Cysts

Abstract: Percutaneous drainage, combined with albendazole therapy, is an effective and safe alternative to surgery for the treatment of uncomplicated hydatid cysts of the liver and requires a shorter hospital stay.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
211
3
14

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 342 publications
(236 citation statements)
references
References 22 publications
4
211
3
14
Order By: Relevance
“…15 Rarely, cyst can grow on to the skin along a sinus tract following surgery or percutaneous drainage of the cyst. 21 Infection of the cyst follows tear in the laminated membrane and soilage of the cyst with bile or blood. Infected hydatid cyst has clinical features of a liver abscess.…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…15 Rarely, cyst can grow on to the skin along a sinus tract following surgery or percutaneous drainage of the cyst. 21 Infection of the cyst follows tear in the laminated membrane and soilage of the cyst with bile or blood. Infected hydatid cyst has clinical features of a liver abscess.…”
Section: Clinical Manifestationsmentioning
confidence: 99%
“…Our results, however, are consistent with other reports of PT. 17,22,[31][32][33][34] In our study, both the groups showed a pattern of rise in titres on IgG ELISA 1 month after the intervention, followed by a gradual fall to baseline values. The rise in titres after either intervention reflects an increase in IgG antibody that occurs owing to small amounts of echinococcal antigens gaining access to the blood stream during the procedure.…”
Section: Discussionmentioning
confidence: 81%
“…Traditionally an echinococcal cyst (hydatid disease) represents an absolute contraindication to LB because piercing of the cyst may be associated with fatal anaphylaxis. However, available data suggest that careful aspiration of these lesions with 19-to 22-gauge needles is relatively safe [21]. Nevertheless, if suspected, consideration and preparation for possible anaphylaxis are warranted.…”
Section: Post-procedural Carementioning
confidence: 99%